AVIATION ACCIDENTS AND INCIDENTS IN USA DURING 23rd SOLAR CYCLE - Polishchuk, Sergii; Chynchenko, Yuriy; Shishkov, Fedor (Proceedings of National Aviation University (archive), 2012)
The influence of space weather phenomenon on aviation safety is considered. The correlation between space weather parameters, such as Ap-index, Wolf’ number and amount of accidents and occurrences in the World and USA is calculated. The main periods of year that characterize the maximum number of accidents and occurrences are determined.